2018
DOI: 10.3389/fenvs.2018.00056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Types and Amounts of Nanoscale Heterogeneity on Bacteria Retention

Abstract: Interaction energy calculations that assume smooth and chemically homogeneous surfaces are commonly conducted to explain bacteria retention on solid surfaces, but experiments frequently exhibit signification deviations from these predictions. A potential explanation for these inconsistencies is the ubiquitous presence of nanoscale roughness (NR) and chemical heterogeneity (CH) arising from spatial variability in charge (CH1), Hamaker constant (CH2), and contact angles (CH3) on these surfaces. We present a meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…Furthermore, differences in AgNP retention on QW and GF sands are not predicted because values of F max were nearly identical (39.4 and 40.1 for QW and GF sand, respectively). Potential explanations for these discrepancies include nanoscale charge heterogeneity and roughness which can locally reduce and/or eliminate the energy barrier (Suresh and Walz, 1996;Bhattacharjee et al, 1998;Hoek et al, 2003;Hoek and Agarwal, 2006;Bradford et al, 2017;Bradford et al, 2018). Nanoscale chemical heterogeneity that is larger than a critical size can create regions on a net unfavorable surface that are favorable for interaction between the colloid and the solid surface due to a local reduction in the energy barrier and an increase in the depth of the primary minimum.…”
Section: Agnp Retention In the Sand With A Rough Surfacementioning
confidence: 99%
“…Furthermore, differences in AgNP retention on QW and GF sands are not predicted because values of F max were nearly identical (39.4 and 40.1 for QW and GF sand, respectively). Potential explanations for these discrepancies include nanoscale charge heterogeneity and roughness which can locally reduce and/or eliminate the energy barrier (Suresh and Walz, 1996;Bhattacharjee et al, 1998;Hoek et al, 2003;Hoek and Agarwal, 2006;Bradford et al, 2017;Bradford et al, 2018). Nanoscale chemical heterogeneity that is larger than a critical size can create regions on a net unfavorable surface that are favorable for interaction between the colloid and the solid surface due to a local reduction in the energy barrier and an increase in the depth of the primary minimum.…”
Section: Agnp Retention In the Sand With A Rough Surfacementioning
confidence: 99%
“…SOM has been found to mask charge heterogeneities and cation bridging with clay particles (Cabal et al, 2010;Han et al, 2008). The interaction of SOM with AgNPs is also expected to be sensitive to the roughness density and height of the AgNP capping agent (Bradford et al, 2017(Bradford et al, , 2018 and the bonding energy between the capping agent and the AgNP (Gunsolus et al, 2015). Additional research is warranted to determine the underlying cause for differences in SOM-AgNP interactions, but a systematic evaluation of these factors is beyond the scope of this work.…”
Section: Agnpmentioning
confidence: 99%
“…However, no research has systematically examined the influence of calcite with impurities from silicate minerals and/or SOM coatings on AgNP transport. Chemical heterogeneities (CH) in such media will produce variations in charge, Hamaker constant (Bradford et al, 2018), and/or hydrophobicity (Tschapek, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the intrinsic surface properties of different types of plastics affect both long and short term bacterial adhesion to their surfaces (Cai et al, 2019). Variations in roughness on a nanoscale and surface chemical heterogeneity further confound assessment of bacterial adhesion onto fomites (Bradford et al, 2018).…”
Section: Fomite Features Influencing Microbial Adhesionmentioning
confidence: 99%